Zanubrutinib, obinutuzumab, and venetoclax with minimal residual disease-driven discontinuation in previously untreated patients with chronic lymphocytic leukaemia or small lymphocytic lymphoma: a multicentre, single-arm, phase 2 trial. Issue 12 (December 2021) - Soumerai, Jacob D; Mato, Anthony R; Dogan, Ahmet; Seshan, Venkatraman E; Joffe, Erel; Flaherty, Kelsey; Carter, Jason; Hochberg, Ephraim; Barnes, Jeffrey A; Hamilton, Audrey M; Abramson, Jeremy S; Batlevi, Connie L; et al.
Summary: Background: We hypothesised that combining zanubrutinib with obinutuzumab and venetoclax (BOVen) as an initial therapy for chronic lymphocytic leukaemia and small lymphocytic lymphoma would lead to high rates of undetectable minimal residual disease (MRD), and we explored MRD as a biomarker for directing treatment duration. Methods: This multicenter, investigator-initiated, single-arm, phase 2 trial took place at two two academic medical centres in the USA. Patients were eligible for the primary cohort if they had treatment-naive chronic lymphocytic leukaemia or small lymphocytic lymphoma, required therapy, and were at least 18 years of age with an Eastern Cooperative Oncology Group performance status up to 2. BOVen was administered in 28 day cycles (oral zanubrutinib at 160 mg twice per day starting in cycle 1 on day 1; intravenous obinutuzumab at 1000 mg on day 1 [split over day 1 with 100 mg and day 2 with 900 mg for an absolute lymphocyte count >25 000 cells per μL or lymph nodes >5 cm in diameter], day 8, and day 15 of cycle 1, and day 1 of cycles 2–8; and oral venetoclax ramp up to 400 mg per day starting in cycle 3 on day 1) and discontinued after 8–24 cycles when prespecified undetectable MRD criteria were met in the peripheral blood and bone marrow. The primary endpoint was the proportion of patients that reached undetectable MRD in both the peripheral blood and bone marrow (flow cytometry cutoff less than one chronic lymphocytic leukaemia cell per 10 000 leukocytes [<10 −4 ]) assessed per protocol. This trial is registered at clinicaltrials.gov (NCT03824483 ). The primary cohort is closed to recruitment, and recruitment continues in the TP53 -mutated mantle cell lymphoma cohort. Findings: Between March 14, 2019, and Oct 10, 2019, 47 patients were screened for eligibility, and 39 patients were enrolled and treated. Median age was 62 years (IQR 52–70) with 30 (77%) of 39 male participants and nine (23%) of 39 female participants. 28 (72%) of 39 patients had unmutated immunoglobulin heavy-chain variable-region and five (13%) of 39 had 17p deletion or TP53 mutation. After a median follow-up of 25·8 months (IQR 24·0–27·3), 33 (89%) of 37 patients (95% CI 75–97) had undetectable MRD in both blood and bone marrow, meeting the prespecified undetectable MRD criteria to stop therapy after a median of ten cycles (IQR 8–12), which includes two cycles of zanubrutinib and obinutuzumab before starting venetoclax. After median surveillance after treatment of 15·8 months (IQR 13·0–18·6), 31 (94%) of 33 patients had undetectable MRD. The most common adverse events were thrombocytopenia (23 [59%] of 39), fatigue (21 [54%]), neutropenia (20 [51%]), and bruising (20 [51%]), and the most common adverse event at grade 3 or worse was neutropenia (seven [18%]) in the intention-to-treat population. One death occurred in a patient with intracranial haemorrhage on day 1 of cycle 1 after initiating intravenous heparin for pulmonary emboli. Interpretation: BOVen was well tolerated and met its primary endpoint, with 33 (89%) of 37 previously untreated patients with chronic lymphocytic leukaemia or small lymphocytic lymphoma reaching undetectable MRD in both peripheral blood and bone marrow despite a median treatment duration of only 10 months, owing to our undetectable MRD-driven treatment discontinuation design. These data support further evaluation of the BOVen regimen in chronic lymphocytic leukaemia and small lymphocytic lymphoma with treatment duration guided by early MRD response kinetics. Funding: Beigene, Genentech (Roche), Grais-Cutler Fund, Lymphoma Research Fund, Lymphoma Research Foundation, American Cancer Society, Farmer Family Foundation, and the National Instititutes of Health and National Cancer Institute.